Separation and recovery method for laminate
Patent Information
- Application Number
- JP2023091211
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-09-26
AI Technical Summary
Existing methods for recycling laminates with polyolefin resin layers face issues of adhesive suspension in desorption liquids, leading to increased energy consumption and environmental burden due to suspended components, and the resulting recycled resin often deteriorates in quality and coloration.
A method involving a laminate structure with a first base layer containing polyethyleneimine or polybutadiene, an adhesive layer with controlled curing agent content, and a polyolefin resin layer, using a desorption liquid with surfactants and antifoaming agents to minimize suspension and facilitate easy reuse.
The method effectively separates and recovers polyolefin resin with reduced contamination, enabling easy reuse of the desorption liquid and producing high-quality recycled resin with minimal mechanical and coloration degradation.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for separating and recovering a polyolefin resin from a laminate having a multi-layer structure. [Background technology]
[0002] In recent years, there has been concern that packaging materials, plastic bottles, and other plastic products made from plastic film discarded or dumped into the ocean as garbage will become microplastics and have an impact on the marine ecosystem.
[0003] In response to this environmental pollution problem, attempts have been made to make packaging materials that are normally made up of multiple different materials easier to recycle by using mono-material packaging materials made up of a single material such as polyolefin. However, packaging materials made only of polyolefin have insufficient retort resistance and light blocking properties, and their applications are limited. In addition, when mono-material packaging materials with printed or adhesive layers are recycled as is, the resulting recycled resin is colored, limiting the uses of the recycled material after recycling. Furthermore, the physical properties of the recycled resin are reduced due to the components derived from the printed or adhesive layers, so it becomes necessary to mix it with virgin resin derived from petroleum, making it difficult to improve the recycling rate.
[0004] Meanwhile, technology has been developed to obtain transparent recycled resin by separating packaging film made of multiple different materials into single-layer films and removing the printed layer and adhesive layer. Regarding the above-mentioned technology, for example, Patent Document 1 discloses a technology in which a laminated film laminated with a reactive adhesive containing a compound having an acidic group, a polyisocyanate composition, and a polyol composition is immersed in an alkaline aqueous solution to separate the laminated film into single-layer films. Patent Document 2 discloses a technique in which a packaging material having a first substrate, a printed layer, a polyurethane-based adhesive layer for removing the second substrate, and the second substrate laminated thereto is immersed in an alkaline aqueous solution to separate and recover the second substrate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 066652 [Patent Document 2] Patent Publication No. 2021-088184 Summary of the Invention [Problem to be solved by the invention]
[0006] That is, in the techniques described in Patent Documents 1 and 2, the adhesive layer, which is a cured product of a reactive adhesive containing a polyol and a polyisocyanate, is swelled and pulverized by an alkaline aqueous solution, thereby enabling the separation and recovery of a monolayer film. However, the coating amount of such a reactive adhesive is generally 1.0 to 5.0 g / m 2 This is about the same as the conventional method, and a large amount of fine pieces of the adhesive layer are generated during the separation process of the laminate, which causes the release liquid to become suspended, and the suspended components adhere to the release film, resulting in a problem of reduced cleanability. Furthermore, if the amount of suspended matter in the eluate increases, the energy required for the filtration and purification processes when reusing the eluate after use increases, which poses a problem of increasing the environmental load. Therefore, an object of the present invention is to provide a method for separating and recovering a polyolefin resin from a laminate while suppressing the suspension (contamination) of the eluent. That is, an object of the present invention is to provide a method for separating and recovering a laminate, which allows easy reuse of the eluent and reduces the environmental load. [Means for solving the problem]
[0007] The method for separating and recovering a laminate according to one embodiment of the present invention is directed to a method for separating and recovering a laminate comprising at least a first base layer, either polyethyleneimine or polybutadiene, and having a mass per unit area of 5 to 100 mg / m 2and a polyolefin resin layer in this order, in a release liquid to separate the polyolefin resin from the laminate, and a recovery step to recover the separated polyolefin resin.
[0008] A method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the laminate has a printed layer between a first base material layer and an adhesive layer.
[0009] A method for separating and recovering a laminate according to one embodiment of the present invention is characterized in that the content of a curing agent contained in the adhesive forming the adhesive layer is 5 mass % or less based on the solid mass of the adhesive.
[0010] A method for separating and recovering a laminate according to one embodiment of the present invention is characterized in that the content of a curing agent contained in the printing ink forming the printed layer is 5 mass % or less based on the solid mass of the printing ink.
[0011] In one aspect of the method for separating and recovering a laminate according to the present invention, the polyolefin resin layer is a layer formed by an extrusion lamination method.
[0012] In one embodiment of the method for separating and recovering a laminate, the adhesive layer has a mass per unit area of 10 to 50 mg / m 2 It is characterized in that:
[0013] A method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the adhesive layer contains polyethyleneimine and polybutadiene in a total amount of 50% by mass or more, based on the mass of the adhesive layer.
[0014] A method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the elution liquid contains water and a surfactant.
[0015] A method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the surfactant has an HLB value of 7 or more.
[0016] The method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the elution liquid further contains an antifoaming agent having an HLB value of 1-3.
[0017] The method for separating and recovering a laminate according to one aspect of the present invention is characterized in that the elution liquid is an alkaline aqueous solution having a temperature of 40° C. to 90° C. and a pH of 12 or higher.
[0018] A laminate separation and recovery method according to one aspect of the present invention is characterized in that the recovery step includes a step of selectively recovering the separated polyolefin resin by gravity separation. Effect of the Invention
[0019] The present invention provides a method for separating and recovering a polyolefin resin from a laminate while suppressing the suspension (contamination) of the eluate, which makes it easy to reuse the eluate in the separation and recovery of the laminate, thereby achieving a further reduction in the environmental load. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention relates to a first base layer, which includes at least one of polyethyleneimine and polybutadiene and has a mass per unit area of 5 to 100 mg / m 2 and a polyolefin resin layer in this order, in a release liquid to separate the polyolefin resin from the laminate, and a recovery step to recover the separated polyolefin resin. Contains either polyethyleneimine or polybutadiene and has a coating amount of 5 to 100 mg / m 2 By combining the laminate having a polyolefin resin layer in contact with the adhesive layer, which is the adhesive layer, with the separation step and recovery step, it is possible to significantly reduce the suspension of the eluted liquid in the separation and recovery of the laminate. Furthermore, when the recovered polyolefin resin is melt recycled, it is possible to obtain a recycled resin with reduced deterioration in mechanical properties and coloration. The present invention will be described in detail below, but these are merely examples of the embodiments of the present invention, and the present invention is not limited to these details as long as it does not depart from the gist of the present invention.
[0021] <Laminate> The laminate in the present invention includes at least a first base layer, either polyethyleneimine or polybutadiene, and has a mass per unit area of 5 to 100 mg / m 2 and a polyolefin resin layer in this order.
[0022] <First base layer> The first substrate layer is not particularly limited, and examples thereof include film or sheet-like plastic substrates, metal foils, papers, etc., which are commonly used in packaging for food products, etc., and may be a laminate of these. Examples of the plastic substrate include films of thermoplastic resins and thermosetting resins, and preferably films of thermoplastic resins. Examples of the thermoplastic resins include polyolefin resins, polyester resins, polyamide resins, polystyrene resins, vinyl chloride resins, vinyl acetate resins, ABS resins, acrylic resins, acetal resins, polycarbonate resins, and cellulose-based plastics.
[0023] Specific examples of plastic substrates include polyolefin resin films such as polyethylene (PE) and biaxially oriented polypropylene (OPP); polyester resin films such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polylactic acid (PLA); polystyrene resin films; polyamide resin films such as nylon 6 and poly-p-xylylene adipamide (MXD6 nylon); polycarbonate resin films; polyacrylonitrile resin films; polyimide resin films; laminates thereof (e.g., nylon 6 / MXD6 / nylon 6, nylon 6 / ethylene-vinyl alcohol copolymer / nylon 6) and mixtures thereof; etc. Among these, those having mechanical strength and dimensional stability are preferred. The thickness of the plastic substrate is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 50 μm.
[0024] The plastic substrate may have a barrier layer made of a vapor-deposited layer of a metal or metal oxide, or an organic layer such as polyvinyl alcohol, for example, a vapor-deposited layer of aluminum, silica, alumina, etc. Commercially available plastic substrates with such a barrier layer include, for example, "GL FILM" (manufactured by Toppan Printing Co., Ltd.) and IB-FILM (manufactured by Dai Nippon Printing Co., Ltd.), which are plastic substrates on which an inorganic vapor deposition layer such as alumina is laminated. An example of the metal foil is aluminum foil, which preferably has a thickness in the range of 3 to 50 μm from an economical point of view. In addition, since aluminum and alumina are soluble in alkaline water, when the separation step described below is carried out using an alkaline aqueous solution as the desorption liquid, aluminum and alumina are dissolved. The vapor-deposited layer or the aluminum foil can be detached from the first substrate layer.
[0025] In the present invention, as described above, a polyolefin resin film such as polyethylene (PE) or biaxially oriented polypropylene (OPP) can be used as the first base layer. By using a polyolefin resin as the first base layer and combining it with the technology of removing the printed layer described later, the polyolefin resin film, which is the first base layer, can be recovered as a transparent polyolefin resin from which the printed layer is removed at the same time as the polyolefin resin layer is separated and recovered, and the total amount of polyolefin resin recovered from the laminate can be increased.
[0026] [Printing layer / Primer layer] The first substrate layer may further have a printed layer. The printed layer is a layer that forms an arbitrary printed pattern for the purpose of decoration, imparting aesthetics, displaying contents, expiration date, manufacturer or seller, etc., and also includes a solid printed layer. The printed layer may be disposed in direct contact with the first substrate, or may be disposed on the first substrate layer via a primer layer. The primer layer and the printed layer will be described below.
[0027] [Primer layer] When the first base layer has a printing layer, a known primer layer may be disposed between the first base layer and the printing layer. The primer layer may be detachable from the first base layer together with the printing layer by immersing in a release liquid described later. By providing such a primer layer, the printing layer can be easily detached from the first base layer in the separation process. This allows the total amount of polyolefin resin recovered from the laminate to be increased when the first base layer is a polyolefin resin film. The primer layer preferably contains a water-soluble resin or a compound having an acidic group (however, excluding water-soluble resins).
[0028] (Water-soluble resin) The water-soluble resin may be any resin that can swell or dissolve in water and be removed from the first base layer. The water may be heated to a temperature of about 25 to 100° C. This allows the primer layer to be removed by water (including warm water). Such resins can be selected from known resins as long as they do not impair water solubility, and examples thereof include water-soluble polyester resins, water-soluble polyamide resins, water-soluble polyimide resins, water-soluble acrylic resins, water-soluble polyurethane resins, water-soluble polyallylamine resins, water-soluble phenolic resins, water-soluble epoxy resins, water-soluble phenoxy resins, water-soluble urea resins, water-soluble melamine resins, polyvinyl alcohol resins, and modified products of these resins. These can be used alone or in combination of two or more. Among them, polyvinyl alcohol (PVA) resins are preferably used from the viewpoints of availability and release properties. When the water-soluble resin has film-forming properties, the water-soluble resin may be used as the binder resin constituting the primer layer.
[0029] As the polyvinyl alcohol resin, in addition to unmodified polyvinyl alcohol, modified polyvinyl alcohol obtained by copolymerizing various monomers during the production of vinyl ester resin and saponifying the copolymer, or various post-modified polyvinyl alcohols obtained by introducing various functional groups into unmodified polyvinyl alcohol by post-modification may be used. Also, modified polyvinyl alcohols further modified may be used. These modifications may be performed within a range that does not impair the water solubility of the polyvinyl alcohol resin. These resins may be used alone or in combination of two or more.
[0030] As the polyvinyl alcohol resin, preferred are resins containing a structural unit having a primary hydroxyl group in the side chain, and ethylene-modified polyvinyl alcohol resins. In terms of excellent adhesion and water solubility, polyvinyl alcohol resins containing structural units having primary hydroxyl groups in the side chains are preferred. The number of primary hydroxyl groups in these structural units is usually 1 to 5, preferably 1 to 2, and more preferably 1. In addition to the primary hydroxyl groups, it is also preferred that the structural units have secondary hydroxyl groups.
[0031] The saponification degree of the polyvinyl alcohol resin used in the present invention (measured according to JIS K 6726) is usually 60 to 100 mol%. The preferred range of the saponification degree varies depending on the modified species. For example, in the case of an unmodified polyvinyl alcohol resin, it is usually 60 to 99.9 mol%, preferably 70 to 99.0 mol%, more preferably 75 to 98.5%. The saponification degree of the modified polyvinyl alcohol resin containing a side chain 1,2-diol structural unit is usually 60 to 99.9 mol%, preferably 65 to 99.8 mol%, more preferably 70 to 99.5 mol%. If the saponification degree is too low, the water solubility tends to decrease. The saponification degree of the ethylene-modified polyvinyl alcohol resin modified with a small amount of ethylene is usually 60 mol% or more, preferably 70 to 99.5 mol%, particularly preferably 75 to 99.0 mol%. The saponification degree within the above range is preferable because it provides excellent water solubility and good releasability, and is also preferable because it provides excellent coatability when forming a primer layer.
[0032] The average degree of polymerization of the polyvinyl alcohol resin (measured in accordance with JIS K 6726) is usually 100 to 3000, preferably 150 to 2000, more preferably 180 to 1000, and particularly preferably 200 to 800. Examples of commercially available products include the JF series manufactured by Nippon Vacuum Acetate & Poval Corporation, and the Poval series and Exeval series manufactured by Kuraray Co., Ltd.
[0033] (Compounds having an acidic group) The compound having an acidic group may be a resin having an acidic group or a low molecular weight compound having an acidic group, which allows the primer layer to be removed with a remover (alkaline aqueous solution). Examples of the resin having an acidic group include a cellulose resin, a urethane resin, a polyamide resin, a vinyl chloride / vinyl acetate copolymer, a ketone resin, a polyester resin, and a (meth)acrylic resin. Examples of the acidic group include a carboxy group, a phosphoric acid group, a sulfo group, a sulfino group, and the like, or an ester or salt thereof. Furthermore, as the resin having an acidic group, a rosin-modified resin having an acid value, such as maleic rosin or fumaric rosin, can be used. In addition, examples of resins having an acidic group that can be used include radical copolymers such as styrene-(meth)acrylic resins, styrene-maleic acid (anhydride) resins, and terpene-maleic acid (anhydride) resins, which are copolymerized with polymerizable monomers having an acidic group, such as polymerizable monomers having a carboxy group, such as itaconic acid, maleic acid, fumaric acid, and cinnamic acid; polymerizable monomers which are acid anhydrides, such as itaconic acid anhydride and maleic acid anhydride; polymerizable monomers having a sulfonic acid group, such as sulfonated styrene; and polymerizable monomers having a sulfonamide group, such as vinylbenzenesulfonamide; and acid-modified polyolefin resins. These may be used alone or in combination of two or more.
[0034] The low molecular weight compound having an acidic group refers to a compound that does not have a molecular weight distribution and has a molecular weight of 1,000 or less. Examples of such compounds include saturated fatty acids such as lauric acid, myristic acid, palmitic acid, margaric acid, and stearic acid; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and sorbic acid; hydroxy acids such as lactic acid, malic acid, and citric acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, gallic acid, mellitic acid, and cinnamic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, and maleic acid; tricarboxylic acids such as aconitic acid; pyruvic acid, oxalic acid, and oxalic acid; Examples of the carboxylic acid derivatives include oxocarboxylic acids such as nitroacetic acid; amino acids and nitrocarboxylic acids; and acid anhydrides such as trimellitic anhydride and pyromellitic anhydride. The low molecular weight compound having an acidic group may be combined with the above-mentioned resin having an acidic group or a known binder resin to form a primer layer.
[0035] [Print layer] There are no limitations on the method for forming the printed layer, and the printed layer can be formed using a known method. The print layer contains a known binder resin and a colorant that are used in printing inks and paints. Examples of the binder resin include fibrous materials such as nitrocellulose and cellulose acetate propionate, chlorinated polypropylene, vinyl chloride-vinyl acetate copolymer, polyester, acrylic, urethane resin and acrylic urethane, polyamide, polybutyral, cyclized rubber, and chlorinated rubber. These resins may be used alone or in combination of two or more. Among these, when the first substrate is a plastic substrate, urethane resin-based, polyester-based, and chlorinated polypropylene-based materials, which have excellent adhesiveness to the plastic substrate, are preferably used.
[0036] The colorant is not particularly limited, and may be inorganic pigments, organic pigments, dyes, metal powders that impart metallic luster, near-infrared absorbing materials, or ultraviolet absorbing materials. Examples of inorganic pigments include colored pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, and graphite; and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. Examples of organic pigments include those listed under generic names in the Color Index, and for example, soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments can be suitably used. The print layer may also contain a pigment derivative or a resin-type dispersant as a dispersant for the colorant.
[0037] The printing layer may have releasability from the release liquid, and may contain, for example, a water-soluble resin or a compound containing an acidic group (excluding water-soluble resins). The water-soluble resin and the compound having an acidic group may be the same as those described in the above section on the primer layer, i.e., (water-soluble resin) and (compound having an acidic group). By providing such a printed layer, the printed layer can be easily detached from the first base layer in the separation step, which makes it possible to increase the total amount of polyolefin resin recovered from the laminate when the first base layer is a polyolefin resin film.
[0038] The printing ink forming the printed layer in the present invention may contain a curing agent within a range that does not impair the effects of the present invention. By containing a curing agent, the curing agent reacts with the binder resin in the printing ink and the hydroxyl groups and carboxyl groups on the surface of the substrate, improving the adhesive strength and content resistance of the laminate. The amount of the curing agent contained in the printing ink is preferably 0% by mass or more and 5% by mass or less based on the solid content mass of the printing ink. When the amount of the curing agent is 5% by mass or less, the curing agent contained in the printed layer can be prevented from migrating excessively to the adhesive layer formed on the printed layer, and the separation property is not impaired. Examples of the curing agent that may be contained in the printing ink include an isocyanate-based curing agent and a silane coupling agent.
[0039] The thickness of the printed layer is preferably 0.1 μm to 100 μm, more preferably 0.1 μm to 10 μm, and further preferably 1 μm to 5 μm.
[0040] <Adhesive layer> The adhesive layer in the present invention is a layer disposed between the first base material layer and the polyolefin resin layer, more specifically, in contact with the first base material layer or the printed layer of the first base material layer. It contains either ethyleneimine or polybutadiene and has a mass per unit area of 5 to 100 mg / m 2 The layer is characterized in that The adhesive layer has a thickness of 5 to 100 mg / m 2 With such a small coating amount, the adhesive layer can exhibit sufficient lamination strength between the first base layer and the polyolefin resin layer described below. Moreover, the adhesive layer can be dissolved and peeled off by immersion in a release liquid to separate the polyolefin resin, and further, the suspension and contamination of the release liquid can be significantly reduced compared to the conventional method.
[0041] [Polyethyleneimine] The polyethyleneimine used in the present invention is a water-soluble polymer obtained by polymerizing ethyleneimine, and is capable of dissolving in water or alcohol. The polyethyleneimine is preferably a branched polyethyleneimine having primary, secondary, and tertiary amino groups in the molecule and having a branched structure in the molecule, and any known polyethyleneimine can be used. Examples of commercially available polyethyleneimines include Epomin SP-003, Epomin SP-006, Epomin SP-012, Epomin SP-018, Epomin SP-200, Epomin HM-2000, Epomin P-1000, and Epomin P-3000 manufactured by Nippon Shokubai Co., Ltd., and LOXANOL MI6721, LOXANOL MI6730, and LOXANOL MI6735 manufactured by BASF. These polyethyleneimines may be used alone or in combination of two or more kinds. From the viewpoint of laminate strength, the number average molecular weight of the polyethyleneimine is preferably 10,000 or more and 180,000 or less, more preferably 30,000 or more and 150,000 or less, and even more preferably 50,000 or more and 100,000 or less.
[0042] [Polybutadiene] The polybutadiene used in the present invention may be any polymer containing butadiene as a constituent unit, and is commercially available under the trade name Seikadyne from Dainichiseika Chemicals Mfg. Co., Ltd. and under the trade name Titabond from Nippon Soda Co., Ltd. The butadiene is preferably derived from 1,2-polybutadiene, and among these, 1,2-polybutadiene modified products such as "Titabond T180E" manufactured by Nippon Soda Co., Ltd. are preferably used from the viewpoint of releasability. This is presumably because "Titabond T180E" is capable of forming an emulsion and has a hydrophilic structure. The polybutadiene may be used alone or in combination of two or more kinds.
[0043] The adhesive layer in the present invention can be provided by using a composition (adhesive) containing either polyethyleneimine or polybutadiene and a medium containing at least one of water and an alcohol-based organic solvent, for example, by a known method such as a gravure coater method or a roll coater method. After applying the adhesive, a drying step may be provided as necessary. The mass per unit area of the adhesive layer is 5 to 100 mg / m from the viewpoint of suppressing contamination of the release liquid. 2 It is important that 2 The adhesive layer applied in an amount less than 100 mg / m is insufficient, making it difficult to maintain the adhesive strength required for the laminate. 2 If it exceeds this limit, the amount dissolved or dispersed in the elution liquid will increase, causing contamination of the elution liquid. The mass per unit area of the adhesive layer is preferably 10 mg / m from the viewpoint of adhesive strength. 2 From the viewpoint of suppressing contamination of the eluent, it is preferably 50 mg / m 2 Less than or equal to 30 mg / m 2 The following is the result. The mass of the adhesive layer can be controlled by adjusting the plate depth and roll transfer amount when applying the adhesive, and by adjusting the solid content of the adhesive.
[0044] The adhesive forming the adhesive layer in the present invention may contain a curing agent within a range that does not impair the effects of the present invention. By containing a curing agent, it reacts with the hydroxyl groups and carboxyl groups on the binder resin in the adhesive, the surface of the printed layer, and the surface of the polyolefin resin, improving the adhesive strength and content resistance of the laminate. The amount of the curing agent contained in the adhesive is preferably 0% by mass or more and 5% by mass or less, based on the solid content mass of the adhesive. When the amount of the curing agent is 5% by mass or less, The dissolution rate and swelling rate of the adhesive layer in the release liquid are not decreased, and separability is not impaired. Examples of the curing agent that may be contained in the adhesive include a water-dispersible isocyanate-based curing agent and a silane coupling agent.
[0045] [Other ingredients] The adhesive layer may contain other components within the range that does not impair the effects of the present invention. Examples of such components include other resins for improving film-forming properties and blocking resistance, leveling agents for improving wettability, and defoamers for suppressing foaming during coating. As the other resin, polyvinyl acetate is preferably used, and examples of commercially available products include the Gohsenil series manufactured by Mitsubishi Chemical Corporation, the Pegal series manufactured by Koatsu Gas Kogyo Co., Ltd., and the VINNAPAS series manufactured by Wacker Polymer. Commercially available leveling agents and defoaming agents include, for example, the Surfynol series manufactured by Nissin Chemical Industry Co., Ltd., and the TEGOGLIDE series and TEGOFOAMEX series manufactured by TEGO.
[0046] The adhesive layer contains either polyethyleneimine or polybutadiene, and preferably contains polyethyleneimine and polybutadiene in a total amount of 50% by mass or more based on the mass of the adhesive layer. From the viewpoint of maintaining both adhesive strength and separability, the total content of polyethyleneimine and polybutadiene in the adhesive layer is preferably 60% by mass or more, more preferably 75% by mass or more.
[0047] <Polyolefin resin layer> The polyolefin resin layer in the present invention may be a layer containing a polyolefin resin as a main component. Since the polyolefin resin has excellent stability, it is excellent in that it does not contaminate the release liquid. Moreover, the main component means that it is 90% by mass or more, preferably 95% by mass or more, based on the mass of the polyolefin resin layer.
[0048] From the viewpoint of adhesive strength, the polyolefin resin layer is preferably formed by extrusion lamination. By laminating using the extrusion lamination method, the adhesive layer has a thickness of 5 to 100 mg / m 2This is preferable because good adhesive strength can be exhibited even with such a small coating amount. For example, the extrusion lamination method includes a method in which a molten polyolefin resin is extruded by an extruder, extruded into a film shape by a jig called a T-die, and then pressed with a press roll and a cooling roll to bond the adhesive layer disposed on a first substrate, thereby laminating a polyolefin resin layer.
[0049] The polyolefin resin used for extrusion lamination can be appropriately selected from known polyethylene resins, polypropylene resins, etc. From the viewpoint of processability, a polyolefin resin having a density of 0.85 to 0.93 g / cm 3 In addition, low-density polyethylene or polypropylene having a melt flow rate (MFR) of 1 to 30 g / 10 min is preferably used. The melting temperature of the polyolefin resin can be adjusted by the melt flow rate of the resin contained, and from the viewpoint of adhesive strength, it is preferably 270° C. or higher immediately below T-die extrusion, more preferably 290° C. or higher. Examples of commercially available polyolefin resins include the Novatec LD series (manufactured by Japan Polyethylene Corporation), the Pedrosene series (manufactured by Tosoh Corporation), and the Novatec PP series (manufactured by Japan Polypropylene Corporation). These polyolefin resins may be used alone or in combination of two or more kinds.
[0050] The thickness of the polyolefin resin layer can be adjusted by changing the extrusion speed depending on the application and purpose. It is possible, but from the viewpoint of achieving a thin film and exhibiting good adhesive strength, the thickness is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm.
[0051] <Production of Laminate> The laminate in the present invention includes at least a first base layer, either polyethyleneimine or polybutadiene, and has a mass per unit area of 5 to 100 mg / m 2The adhesive layer may be formed by laminating a molten polyolefin resin on the adhesive layer of the first base material layer having an adhesive layer containing either polyethyleneimine or polybutadiene by extrusion lamination. The adhesive layer may be formed by applying an adhesive containing polyethyleneimine and / or polybutadiene by a known method such as a gravure coater method or a roll coater method.
[0052] [Sealant base layer] The laminate of the present invention may further have a sealant substrate layer. Examples of the sealant substrate include polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), acid-modified polyethylene, polypropylene (PP), acid-modified polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-(meth)acrylic acid copolymer, and ionomer. As described above, the sealant substrate layer may be a polyolefin resin film such as polyethylene or polypropylene. When the sealant substrate is a polyolefin resin film, the sealant substrate can be recovered together with the polyolefin resin when the polyolefin resin is separated and recovered, and the total amount of polyolefin resin recovered from the laminate can be increased, which is preferable.
[0053] The position and lamination method of the sealant substrate layer are not particularly limited, but for example, it can be provided by a known method such as dry lamination or extrusion lamination on the surface opposite to the adhesive layer in contact with the first substrate layer. A known adhesive can be used as the adhesive used for dry lamination, and a releasable adhesive that is released by a release liquid may be used. By using a releasable adhesive, the sealant substrate can be separated and recovered.
[0054] For example, the sealant substrate layer can be provided on the surface opposite to the adhesive layer in contact with the polyolefin resin layer described above. In this case, the sealant substrate layer can be laminated by extrusion laminating the adhesive layer surface of the first substrate layer having the adhesive layer and the sealant substrate via a molten polyolefin resin.
[0055] When the sealant substrate is a polyolefin resin film and is configured to be disposed in contact with the polyolefin resin layer, the sealant substrate layer and the polyolefin resin layer can be separated and recovered together without separation between them.
[0056] For example, the sealant substrate layer may have a barrier layer made of a vapor-deposited layer of a metal or metal oxide. Examples of the vapor-deposited layer include vapor-deposited layers of aluminum, silica, alumina, etc. Since the vapor-deposited layer dissolves in an alkaline aqueous solution, when the sealant substrate is a polyolefin resin film, it can be recovered together with the polyolefin resin.
[0057] The thickness of the sealant base layer is not particularly limited, but is preferably 10 to 200 μm, more preferably 15 to 150 μm, in consideration of processability into packaging materials, heat sealability, etc. In addition, the sealant base material can be provided with projections and recesses having a height difference of about several μm to improve slipperiness and packaging properties. The dressing material may be provided with tearability.
[0058] [Other layers] The laminate of the present invention may further have a known layer within a range that does not impair the effects of the present invention. Examples of the layer that may be included include an adhesive layer, a plastic substrate layer, a metal foil, paper, an overcoat layer, and a heat seal layer, and may also have a vapor-deposited layer of a metal or metal oxide.
[0059] Specific examples of the laminate of the present invention will be given below. First base material layer / adhesive layer / polyolefin resin layer First base layer / printed layer / adhesive layer / polyolefin resin layer / sealant base layer First base layer / primer layer / printed layer / adhesive layer / polyolefin resin layer / sealant base layer First base layer / printed layer / adhesive layer / polyolefin resin layer / sealant base layer First base layer / printed layer / adhesive layer / polyolefin resin layer / deposited film layer / adhesive layer / polyolefin resin layer / sealant base layer Sealant base layer / polyolefin resin layer / adhesive layer / first base layer / printing layer / adhesive layer / polyolefin resin layer
[0060] <Method for separating and recovering laminate> The method for separating and recovering a laminate of the present invention comprises a separation step of immersing the above-mentioned laminate in a release liquid to separate the polyolefin resin from the laminate, and a recovery step of recovering the separated polyolefin resin. In the present invention, when the separated and recovered polyolefin resin is reused as a recycled substrate or a regenerated substrate, it is preferable that the recovered polyolefin resin contains fewer components other than the polyolefin resin (for example, components derived from the first substrate, adhesive, printing ink, etc.). Furthermore, when another layer contained in the laminate, such as the first substrate or a sealant substrate provided in contact with the polyolefin resin layer, is made of polyolefin, these resins can also be recovered together with the polyolefin resin, which is preferable because it allows the total amount of polyolefin resin to be recovered to be increased. The amount of polyolefin resin recovered (recovery rate) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the mass of all plastic substrates contained in the laminate.
[0061] [Separation process] The eluent used in the separation step contains either polyethyleneimine or polybutadiene and has a mass per unit area of 5 to 100 mg / m 2Any adhesive layer that can separate the polyolefin resin by dissolving or swelling the adhesive layer that is the first base material layer or the adhesive layer that is the first base material layer can be used. By immersing the laminate in the release liquid, the adhesive layer dissolves or swells and is peeled off from the first base material layer and the adhesive layer, and the adhesive layer can be separated from the first base material layer.
[0062] (Removal solution) Examples of such a release liquid include water, an alkaline aqueous solution, an acidic aqueous solution, and a fluorine-based solvent, and may contain a surfactant and / or an antifoaming agent. From the viewpoint of reducing the environmental load and maintaining the properties of the recovered polyolefin resin, the elution liquid is preferably water, an aqueous solution containing water such as an alkaline aqueous solution or an acidic aqueous solution, more preferably water or an alkaline aqueous solution, still more preferably one containing a surfactant having an HLB value of 7 or more, and particularly preferably one containing a surfactant having an HLB value of 7 or more and an antifoaming agent having an HLB value of 1 to 3. The elution liquid may be heated, and from the viewpoint of separation, the temperature is preferably 40°C to 90°C. The HLB value is an index value relating to affinity for water and oil, with a substance having no hydrophilic groups having an HLB value of 0 and a substance having only hydrophilic groups having an HLB value of 20. The concept of HLB was proposed by William Griffin of the Atlas Powder Company in 1949, and several methods for determining the HLB value by calculation have been proposed. In the present invention, the HLB value can be calculated using the Griffin method from the following formula. Formula: HLB = 20 x [(molecular weight of hydrophilic group contained in surfactant) / (molecular weight of surfactant)] Examples of the hydrophilic group contained in the surfactant include a hydroxyl group and an ethyleneoxy group.
[0063] <Alkaline aqueous solution> The alkaline aqueous solution is preferably an aqueous solution containing a basic compound and having a pH of 12 or more. The basic compound is not particularly limited, and for example, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3) are preferably used, but are not limited thereto. More preferably, it is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide. The alkaline aqueous solution preferably contains 0.5 to 20 mass %, more preferably 1 to 15 mass %, and further preferably 3 to 15 mass % of a basic compound in the aqueous solution. When the concentration is within the above range, the adhesive layer is efficiently dissolved or swollen, and separation of the polyolefin resin is excellent.
[0064] Surfactants Surfactants with an HLB value of 7 or more play a role in improving the separation properties of adhesive layers, etc. This is thought to be because the release liquid containing a surfactant with an HLB value of 7 or more makes it easier for the release liquid to penetrate into the adhesive layer, accelerating separation. The content of the surfactant in the elution liquid is preferably in the range of 0.001 to 10 mass %, more preferably in the range of 0.03 to 3 mass %, based on the mass of the elution liquid.
[0065] The types of surfactants having an HLB value of 7 or more include, for example, nonionic, anionic, cationic, and amphoteric, and the appropriate type and blending amount can be selected according to the required properties. From the viewpoint of releasing property and foaming property, it is preferable to use at least one type selected from the group consisting of anionic surfactants and nonionic surfactants. In addition, it is preferable that the surfactant has a structure with an alkylene oxide (hereinafter also referred to as AO) added thereto, since this improves releasing property.
[0066] Defoaming Agent In the present invention, the antifoaming agent refers to one having an HLB value in the range of 1 to 3, and when used in combination with the above-mentioned surfactant having an HLB value of 7 or more, it exhibits good antifoaming properties and can suppress foaming caused by the surfactant. This improves the stirring speed by suppressing foaming during desorption, and suppresses the interference with separation caused by foam during gravity separation described below, making it easier to recover the floating polyolefin resin. The above-mentioned defoaming agent includes, for example, a silicone-based compound and a non-silicone-based compound. The defoaming agent may be used alone or in combination of two or more kinds. The content of the antifoaming agent in the eluent is preferably in the range of 0.0001 to 3 mass %, more preferably in the range of 0.01 to 1 mass %, based on the mass of the eluent.
[0067] (Shredding process) The release liquid penetrates from the end portion of the laminate and contacts the adhesive layer, dissolving or swelling the adhesive layer, thereby dissolving the polyolefin resin layer at the interface between the first base layer and the polyolefin resin layer. The polyolefin resin is detached from the other layers. Therefore, in order to efficiently proceed with the separation step, it is preferable to have a shredding step in which the laminate is cut or crushed to expose the adhesive layer on the cross section before the separation step. By providing the shredding step, the polyolefin resin can be separated from the first substrate and the other layers to which the polyolefin resin layer is in contact in a shorter time. The method for shredding or crushing the laminate is not particularly limited, and examples thereof include methods using a jaw crusher, impact crusher, cutter mill, stamp mill, ring mill, roller mill, jet mill, and hammer mill.
[0068] The immersion time in the release liquid is preferably 1 minute to 24 hours, more preferably 1 minute to 12 hours, and further preferably 1 minute to 6 hours. The amount of the release liquid used is preferably 10 to 100 times, and more preferably 25 to 100 times, the mass of the laminate, from the viewpoint of the quality of the recycled plastic and the processing efficiency. In order to improve the separation efficiency, it is preferable to stir or circulate the release liquid. The rotation speed for stirring is preferably 80 to 3000 rpm, and more preferably 200 to 2000 rpm.
[0069] [Recovery process] The method for recovering the polyolefin resin is not particularly limited, and for example, the polyolefin resin can be selectively recovered using a gravity separation method. In the gravity separation method, the polyolefin resin separated in the separation step can be separated from the printed layer and the first substrate by utilizing the difference in specific gravity. In addition, when the first substrate or the sealant substrate contained in the laminate is made of polyolefin and the printed layer can be removed in the separation step, it can be recovered together with the polyolefin resin layer.
[0070] (Removal process / cleaning process) In the separation and recovery method of the present invention, a removal step of removing the substrate to which the printed layer or adhesive layer is attached may be included after the recovery step. The removal method is not particularly limited, and examples thereof include a method using an optical sensor such as an infrared sensor or a color sorting sensor. In the separation and recovery method of the present invention, after the recovery step, a washing step may be provided in which the recovered polyolefin resin is washed with water to wash away any adhering elution liquid or impurities, and a drying step may be further provided as necessary. The order of the removing step and the washing step is not limited, and either step may be carried out first.
[0071] <Recycling polyolefin resin> The polyolefin resin recovered by the separation and recovery method of the present invention can be pelletized and reused as a recycled resin. The pelletizing step is a step in which various additives are added as necessary, the mixture is mixed in a Henschel mixer, a tumbler, a disperser or the like, and then melt-kneaded. Examples of melt kneading apparatus include batch kneaders such as kneaders, roll mills, super mixers, Henschel mixers, Schuggi mixers, vertical granulators, high-speed mixers, Furmatrix, ball mills, steel mills, sand mills, vibration mills, attritors, and Banbury mixers, twin-screw extruders, single-screw extruders, and rotor-type twin-screw kneaders. The shape of the pelletized material is not particularly limited, and may be any of pellets, powder, granules, beads, and the like.
[0072] The recycled resin may further contain a master batch. The master batch is not particularly limited as long as it has compatibility with the recycled resin, and generally, a mixture of a thermoplastic resin such as a polyethylene resin or a polypropylene resin and a colorant can be used. The thermoplastic resin contained in the master batch may be used alone or in combination of two or more kinds.
[0073] The colorant is not particularly limited as long as it is one that is generally used in masterbatches, and examples thereof include inorganic pigments such as titanium oxide, chrome titanium iron, red iron oxide, ultramarine, and carbon black; and organic pigments such as azo pigments, quinacridone pigments, perylene pigments, diketopyrrolopyrrole pigments, and phthalocyanine pigments.
[0074] The master batch may contain, within the scope not impairing the effects of the present invention, a metallic soap of an alkali metal, an alkaline earth metal, or zinc, hydrotalcite, a nonionic surfactant, a cationic surfactant, an anionic surfactant, an amphoteric surfactant, an antistatic agent, a flame retardant such as a halogen-based, phosphorus-based, or metal oxide, a lubricant such as ethylene bis alkyl amide, an antioxidant, an ultraviolet absorber, or a filler. EXAMPLES
[0075] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, "parts" and "%" represent "parts by mass" and "% by mass" unless otherwise noted.
[0076] The methods for measuring the molecular weight, molecular weight distribution, acid value and hydroxyl value of the synthesized polyester polyols P1 and P2 and urethane varnishes B1 and B3 are shown below. <Molecular weight and molecular weight distribution> The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) were measured by GPC (gel permeation chromatography) and calculated as molecular weights using polystyrene as a standard substance. The measurement conditions are shown below. GPC equipment: Showa Denko Shodex GPC-104 Columns: The following columns were used in series connection: Showa Denko Shodex LF-404 x 2 Showa Denko Shodex LF-G Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 0.3mL / min
[0077] <Acid value, hydroxyl value> The acid value and hydroxyl value were measured in accordance with JIS K 0070 (1992).
[0078] <Adhesive manufacturing> (Manufacture of adhesive T1) 0.70 parts of Epomin P-1000 (polyethyleneimine solution manufactured by Nippon Shokubai Co., Ltd.), 29.79 parts of water, and 69.51 parts of ethanol were mixed to obtain adhesive T1 having a non-volatile content of 0.2%.
[0079] (Manufacture of adhesives T2 to T14) Except for changing the raw materials and blending compositions shown in Table 1, adhesives T2 to T14 were obtained in the same manner as adhesive T1.
[0080] [Table 1]
[0081] The abbreviations in Table 1 are as follows: Epomin P-1000 (polyethyleneimine solution manufactured by Nippon Shokubai Co., Ltd.): Number average molecular weight 70,000, non-volatile content 30% by mass Epomin SP-018 (polyethyleneimine manufactured by Nippon Shokubai Co., Ltd.): Number average molecular weight 1,800 Epomin SP-200 (polyethyleneimine manufactured by Nippon Shokubai Co., Ltd.): Number average molecular weight 10,000 Titabond T-180E (emulsion-type polybutadiene manufactured by Nippon Soda Co., Ltd.): Non-volatile content 10% by mass Gosenil M50-Z8 (polyvinyl acetate manufactured by Mitsubishi Chemical Corporation) non-volatile content 50% by mass Pegal 150 (polyvinyl acetate manufactured by Koatsu Gas Kogyo Co., Ltd.) non-volatile content 42% by mass KBM-403 (3-glycidoxypropyltrimethoxysilane manufactured by Shin-Etsu Chemical Co., Ltd.)
[0082] (Manufacture of adhesives T15 to T17) The polyurethane adhesives described in JP 2021-088184 A were used as adhesives T15 to T17. Specifically, 90 parts of a solution of polyester polyol (P1), 10 parts of a solution of polyester polyol (P2), and 8 parts of a solution of polyisocyanate (C1) shown below were mixed, and ethyl acetate was added to prepare an adhesive solution with a non-volatile content of 30%. The adhesive solution was further diluted with ethyl acetate to a non-volatile content of 2% to obtain adhesive T15, similarly diluted to a non-volatile content of 6% to obtain adhesive T16, and diluted to a non-volatile content of 18% to obtain adhesive T17.
[0083] 《Synthesis of polyester polyol P1》 In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 124 parts of ethylene glycol, 212 parts of neopentyl glycol, 368 parts of 1,6-hexanediol, 645 parts of isophthalic acid, 36 parts of adipic acid and 265 parts of sebacic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 35 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 12.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol P1 with a number average molecular weight of 9,000 and an acid value of 30.3 mg KOH / g.
[0084] 《Synthesis of polyester polyol P2》 A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube was charged with 58 parts of ethylene glycol, 412 parts of diethylene glycol, 343 parts of neopentyl glycol, 517 parts of isophthalic acid and 393 parts of adipic acid, and the mixture was heated to 250 ° C. while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 4.0 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the mixture was reacted at 180 ° C. for about 2 hours, and then diluted with ethyl acetate until the non-volatile content was 50%, to obtain a solution of partially acid-modified polyester polyol P2 with a number average molecular weight of 2,000 and an acid value of 23.5 mg KOH / g.
[0085] <Adjustment of Polyisocyanate C1> Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate to adjust the nonvolatile content to 50% and NCO% to 9.6%, to obtain a solution of polyisocyanate C1.
[0086] <Printing ink manufacturing> (Manufacturing of printing ink I1) 30 parts of polyurethane varnish B1 (KL-593 manufactured by Arakawa Chemical Co., Ltd.: polyester polyether combined polyurethane varnish solid content concentration 30%), 10 parts of vinyl chloride-vinyl acetate copolymer resin varnish (Solvine TAO manufactured by Nisshin Chemical Co., Ltd.: ethyl acetate solution with solid content concentration 30%), 10 parts of indigo pigment (Leonol Blue FG7330 manufactured by Toyo Color Co., Ltd.), and 20 parts of a mixed solvent of normal propyl acetate / isopropyl alcohol = 70 / 30 (mass ratio) were stirred and mixed, and then dispersed for 20 minutes using a sand mill. Then, 30 parts of the mixed solvent were stirred and mixed to obtain printing ink I1.
[0087] (Manufacturing of printing ink I2) Printing ink was obtained in the same manner as printing ink I1, except that polyurethane varnish B1 was changed to polyester varnish B2 (Vylon 200 manufactured by Toyobo Co., Ltd.: polyester varnish solids concentration 30% ethyl acetate solution). 3 parts of hexamethylene diisocyanate bifunctional prepolymer (Duranate D101 manufactured by Asahi Kasei Co., Ltd., solution diluted with ethyl acetate to a solids concentration of 50%) was added to 100 parts of this printing ink to obtain printing ink I2.
[0088] (Manufacturing of printing ink I3) To 100 parts of printing ink I1, 3 parts of hexamethylene diisocyanate bifunctional prepolymer (Asahi Kasei Corporation's Duranate D101, a solution diluted with ethyl acetate to a solids concentration of 50%) was added to obtain printing ink I3.
[0089] <Production of primer composition> (Production of polyurethane resin B3) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 135.7 parts of PPA (a polyester polyol composed of a polycondensate of propylene glycol and adipic acid and having a number average molecular weight of 2,000), 13.6 parts of PPG (a polyether polyol composed of polypropylene glycol and having a number average molecular weight of 2,000), 28.3 parts of 2,2-dimethylolpropanoic acid, 106.7 parts of isophorone diisocyanate, and 200 parts of normal propyl acetate were charged while introducing nitrogen gas, and the mixture was reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at its end. Next, a mixture of 16.7 parts of 2-(2-aminoethylamino)ethanol and 350 parts of isopropyl alcohol was added dropwise at room temperature over 60 minutes, and then the mixture was reacted at 70° C. for 3 hours to obtain a polyurethane resin solution. To the obtained polyurethane resin solution, 150 parts of normal propyl acetate was added to adjust the solid content, and a solution of polyurethane resin B3 was obtained with a solid content concentration of 30%, a weight average molecular weight of 30,000, Mw / Mn=3.0, an acid value of 38.3 mgKOH / g, and a hydroxyl value of 30.5 mgKOH / g.
[0090] (Production of primer composition S1) 87 parts of polyurethane resin B3 solution, 5 parts of ethyl acetate, 5 parts of isopropyl alcohol, and 3 parts of silica particles (P-73 manufactured by Mizusawa Chemical Industries, Ltd.: hydrophilic silica particles having an average particle size of 3.8 μm) were stirred and mixed using a disper to obtain primer composition S1.
[0091] (Production of primer composition S2) Five parts of polyvinyl alcohol resin (JF-03 manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.) and 95 parts of water were mixed with stirring at 95° C. using a disper to obtain a primer composition S2.
[0092] (Preparation of primer composition S3) 30 parts of polyurethane varnish B1, 10 parts of vinyl chloride-vinyl acetate copolymer resin varnish, 2 parts of pyromellitic anhydride, and 58 parts of a mixed solvent of normal propyl acetate / isopropyl alcohol = 70 / 30 (mass ratio) were stirred and mixed using a disper to obtain primer composition S3.
[0093] <Production of Laminate> (Laminate L1) Adhesive T1 was applied to the treated surface of OPP (corona-treated biaxially oriented polypropylene film, thickness 20 μm) using a gravure coater equipped with a gravure plate with a plate depth of 15 μm, and dried at 80°C to form an adhesive layer. LDPE (low-density polyethylene manufactured by Japan Polyethylene Co., Ltd.: Novatec LD LC520) was extrusion laminated onto the adhesive layer at a melting temperature of 310°C, and pressed onto CPP (corona-treated unoriented polypropylene film, thickness 30 μm) to obtain laminate L1. The mass per unit area of the adhesive layer (coating amount) was 10 mg / m 2 The thickness of the LDPE layer was 15 μm.
[0094] (Laminated body L2) Except for the changes shown in Table 2, a laminate L2 was obtained in the same manner as for laminate L1.
[0095] (Laminate L3) Diluted printing ink I1 was printed on the OPP-treated surface using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to form a printed layer. Then, adhesive T1 was applied onto the printed layer using a gravure coater equipped with a gravure plate with a plate depth of 15 μm, and dried at 80°C to form an adhesive layer. LDPE was extrusion laminated onto the adhesive layer at a melt temperature of 310°C, and pressed onto the CPP to obtain laminate L3. The coating amount of the adhesive layer was 10 mg / m 2 The thickness of the LDPE layer was 15 μm.
[0096] (Laminates L4~L15, L17~L20, L24~L29) Laminates L4 to L15, L17 to L20, and L24 to L29 were obtained in the same manner as for laminate L3, except for the changes shown in Table 2. Note that laminates L19, L27, and L29 were produced without pressure bonding the sealant substrate.
[0097] (Laminate L16) Diluted printing ink I1 was printed on the OPP-treated surface using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to form a printed layer. Adhesive T1 was applied onto the printed layer using a gravure coater equipped with a gravure plate with a plate depth of 15 μm, and dried at 80°C to form an adhesive layer. LDPE was extrusion laminated onto the adhesive layer at a melt temperature of 310°C, and pressed against the vapor-deposited surface of VMPET to form a laminate. Next, adhesive T1 was applied to the PET surface of the VMPET using a gravure coater equipped with a gravure plate with a plate depth of 15 μm, and dried at 80°C to form an adhesive layer. LDPE was extrusion laminated onto the adhesive layer at 310°C, and pressed onto the CPP to obtain laminate L16. The coating amount of each adhesive layer was 10 mg / m 2 The thickness of each of the LDPE layers was 15 μm.
[0098] (Laminate L21) Primer composition S1 diluted with ethyl acetate to 1% non-volatile content was printed on the OPP-treated surface using a gravure plate with a plate depth of 15 μm and dried at 50° C. to form a primer layer. Printing ink I1 was printed on the primer layer using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm and dried at 50° C. to form a printed layer. Adhesive T1 was applied on the printed layer using a gravure coater equipped with a gravure plate with a plate depth of 15 μm and dried at 80° C. to form an adhesive layer. Then, LDPE was extrusion laminated onto the adhesive layer at a melting temperature of 310°C, and pressed onto the CPP to obtain a laminate L21. The coating amount of each adhesive layer was 10 mg / m 2 The thickness of each of the LDPE layers was 15 μm.
[0099] (Laminates L22 and L23) Laminates L22 and L23 were obtained in the same manner as for laminate L21, except for the changes shown in Table 2. Note that water was used to dilute primer S2 in laminate L22.
[0100] (Laminates LL1, 8, 10) Comparative laminates LL1, 8, and 10 were obtained in the same manner as laminate L1, except that the materials and melting temperatures were changed to those shown in Table 3 and no adhesive layer was used. Note that laminate LL10 was produced without pressure bonding the sealant substrate.
[0101] (Laminates LL2, 9, 11, 12) Comparative laminates LL2, 9, 11, and 12 were obtained in the same manner as laminate L1, except that the materials and melting temperatures were changed to those shown in Table 3, and instead of using an adhesive layer, a corona discharge treatment was applied to the printed layer immediately before extrusion lamination. Note that laminate LL11 was produced without pressure bonding the sealant substrate.
[0102] (Laminate LL3~7) Comparative laminates LL3 to LL7 were obtained in the same manner as for laminate L1, except that the materials and melting temperatures were changed to those shown in Table 3. Note that laminate LL7 was produced without pressure bonding the sealant base material.
[0103] (Laminate LL13) After forming a printing layer in the same manner as for laminate L1, the printed layer was laminated to the CPP using adhesive T4 without a polyolefin resin layer in a dry laminator equipped with a gravure plate with a plate depth of 45 μm to obtain a comparative laminate LL13. The coating amount of the adhesive layer was 300 mg / m 2 It was.
[0104] (Laminate LL14) A comparative laminate LL14 was obtained in the same manner as the laminate LL13, except that the adhesive T4 was changed to the adhesive T17. The coating amount of the adhesive layer was 2700 mg / m 2 It was.
[0105] <Adhesive strength of laminate> The obtained laminate was cut into a width of 1.5 cm, and the adhesive strength was measured by peeling at 90° using an Intesco tensile tester. A: Adhesive strength is 1.0N or more B: Adhesive strength is 0.6N or more and less than 1.0N C: Adhesive strength is 0.3N or more and less than 0.6N D: Adhesive strength is less than 0.3N
[0106] [Table 2]
[0107] [Table 3]
[0108] The abbreviations in Tables 2 and 3 are shown below. Note that the * mark in the tables indicates the base material recovered as polyolefin resin. (first base layer) OPP: Corona-treated biaxially oriented polypropylene film, thickness 20 μm PET: Corona-treated polyethylene terephthalate film, thickness 12 μm Paper: Coated cup paper, 270 g / m 2 (Polyolefin resin layer) LDPE: Novatec LD LC520 (low density polyethylene manufactured by Japan Polyethylene Corporation) PP: Novatec PP FL02A (polypropylene made by Japan Polyethylene Corporation) (Vapor deposition film layer) VMPET: Aluminum-deposited polyethylene terephthalate film, thickness 12 μm (Sealant base layer) CPP: Corona-treated non-oriented polypropylene film, thickness 30 μm VMCPP: Aluminum-deposited non-oriented polypropylene film, thickness 25μm LLDPE: Corona-treated linear low-density polyethylene film, thickness 50 μm
[0109] The laminates LL1 to 3, 5, and 8 to 10 had extremely low adhesive strength and could not be produced, so they were not subjected to the subsequent separation and recovery of the laminate.
[0110] <Separation and recovery of laminate> First, the eluent used for separating and recovering the laminate was prepared by mixing according to the following formulation and conditions. [Table 4]
[0111] The abbreviations in Table 4 are as follows: Surfactant Y1: POE stearyl ether (POE addition number: 12, HLB value: 13.9) Surfactant Y2: Sodium lauryl sulfate (HLB value > 20) Defoamer T1: BYK-1650 (Silicone emulsion manufactured by BYK Chemie, solids concentration 27.5%)
[0112] [Example 1] 1 kg of the release liquid W1 was prepared, and 0.02 kg of the laminate L1 cut into 5 mm squares was added to the release liquid. The adhesive layer was released and separated between the first substrate and the LDPE by stirring at 800 rpm for 180 minutes using a disper. After stopping the stirring and leaving it to stand for 30 minutes, the polyolefin component (OPP and a mixture of LDPE / CPP) that floated due to its specific gravity was scooped up with a sieve, washed with water, and then dried in an oven. The remaining release liquid was filtered through an 80 mesh.
[0113] [Examples 2 to 35, Comparative Examples 1 to 14] The laminate was separated and recovered in the same manner as in Example 1, except that the laminate and the elution liquid were changed to those shown in Table 5, to obtain recovered polyolefin. Removed.
[0114] <Evaluation> The separation property, the turbidity of the eluate after separation and recovery, and the recovery rate of polyolefin were evaluated as follows.
[0115] [Separability] Ten pieces of separated polyolefin resin or laminates of polyolefin resin layer and sealant base material layer were randomly sampled from the laminate during stirring 60 minutes, 120 minutes, and 180 minutes after stirring. After washing with water and drying, the ATR-IR of the polyolefin resin surface was measured to confirm that the absorption peak of the adhesive had disappeared in all ten pieces. The results were evaluated according to the following criteria. (Evaluation Criteria) A (Excellent): After 60 minutes of stirring, the absorption peak of the adhesive layer disappears. B (Good): After 120 minutes of stirring, the absorption peak of the adhesive layer disappears. C (passable): After stirring for 180 minutes, the absorption peak of the adhesive layer disappears. D (Fail): After 180 minutes of stirring, disappearance of the absorption peak of the adhesive layer was not confirmed, or the laminate was not separated and no transparent film to be measured existed.
[0116] [Turbidity of the desorption solution] After filtering through an 80 mesh filter, 200 ml of the supernatant was sampled and the turbidity was measured by formazin nephelometry in accordance with JIS K0101. (Evaluation Criteria) A (Excellent): Turbidity is less than 50 NTU B (Good): Turbidity is 50 NTU or more and less than 100 NTU C (Acceptable): Turbidity is 100NTU or more and less than 300NTU D (Not acceptable) Turbidity: 300 NTU or more
[0117] [Recovery rate] The recovery rate was calculated and evaluated using the following formula. Formula) Recovery rate (%) = mass of recovered transparent polyolefin resin / total mass of plastic components in laminate × 100 (Evaluation Criteria) A: Recovery rate is 80% or more B: Recovery rate is 50% or more but less than 80% C: Recovery rate is less than 50%
[0118] [Table 5]
[0119] According to the above evaluation results, the composition containing either polyethyleneimine or polybutadiene and having a coating amount of 5 to 100 mg / m 2 By combining a laminate having a polyolefin resin layer in contact with an adhesive layer, a separation step, and a recovery step, it is possible to separate and recover a polyolefin resin with few adhering components while significantly reducing the suspension of the eluted liquid. As a result, when the recovered polyolefin resin is melted and recycled, a recycled resin with reduced deterioration in mechanical properties and coloring can be obtained. In particular, the adhesive application amount is 10 to 50 mg / m 2 In Examples 8 to 10, 24, and 25, in which the printing ink and adhesive did not contain a curing agent and polyethyleneimine having a number average molecular weight of 50,000 or more and 100,000 or less was used as the adhesive, good adhesive strength was exhibited, while the separation property of the polyolefin resin was excellent and the turbidity of the release liquid was suppressed. The adhesive layer contains either polyethyleneimine or polybutadiene, but the coating weight is 100 mg / m 2 In Comparative Examples 1 and 6, which exceeded the above range, the polyolefin resin was able to be separated, but the eluate was largely suspended. In Comparative Examples 2, 3, and 7, which used a polyurethane adhesive with releasability, the polyolefin resin was able to be separated, but the released adhesive components caused the released liquid to become significantly suspended, and the adhesive layer was applied in an amount of 100 mg / m 2 Even so, it was largely suspended (Comparative Example 2). In the comparative laminates LL1, LL2, and LL8 to LL12, the adhesive strength was insufficient, or the polyolefin resin layer did not separate (Comparative Examples 4 and 5).
Claims
1. At least the first base layer contains either polyethyleneimine or polybutadiene and has a mass per unit area of 5 to 100 mg / m 2 and a polyolefin resin layer in this order, in a release liquid to separate the polyolefin resin from the laminate; and a recovery step to recover the separated polyolefin resin.
2. The method for producing recycled polyolefin resin according to claim 1 , wherein the laminate comprises a printed layer between the first substrate layer and the adhesive layer.
3. The method for producing recycled polyolefin resin according to claim 1 or 2, wherein the content of the curing agent contained in the adhesive forming the adhesive layer is 5 mass% or less based on the solid mass of the adhesive.
4. The method for producing recycled polyolefin resin according to claim 2, wherein the content of the curing agent contained in the printing ink forming the printed layer is 5 mass% or less based on the solid content mass of the printing ink.
5. A method for producing recycled polyolefin resin as described in claim 3, wherein the content of hardener contained in the printing ink that forms the printed layer is 5 mass% or less based on the solid mass of the printing ink.
6. The method for producing recycled polyolefin resin according to claim 1 or 2, wherein the polyolefin resin layer is a layer formed by an extrusion lamination method.
7. The adhesive layer has a mass per unit area of 10 to 50 mg / m 2 The method for producing the recycled polyolefin resin according to claim 1 or 2.
8. The method for producing recycled polyolefin resin according to claim 1 or 2, wherein the adhesive layer contains 50% by mass or more of polyethyleneimine and polybutadiene in total, based on the mass of the adhesive layer.
9. The method for producing recycled polyolefin resin according to claim 1 or 2, wherein the desorption liquid contains water and a surfactant.
10. The method for producing recycled polyolefin resin according to claim 9, wherein the surfactant has an HLB value of 7 or more.
11. The method for producing recycled polyolefin resin according to claim 10, wherein the elution liquid further contains an antifoaming agent having an HLB value of 1 to 3.
12. The method for producing recycled polyolefin resin according to claim 1 or 2, wherein the desorption liquid is an alkaline aqueous solution having a temperature of 40°C to 90°C and a pH of 12 or more.
13. The method for producing a recycled polyolefin resin according to claim 1 or 2, wherein the recovery step includes a step of sorting and recovering the separated polyolefin resin by gravity separation.